Determination of ‘Palmer’ mango maturity indices using portable near infrared (VIS-NIR) spectrometer - dos Santos Neto, João Paixão [UNESP]; de Assis, Mateus Wagner Dantas; Casagrande, Izabella Parkutz [UNESP]; Cunha Júnior, Luis Carlos; de Almeida Teixeira, Gustavo Henrique [UNESP] (Elsevier, 2017)
‘Palmer’ mango cultivar is a late season variety which is greatly accepted by European consumers. However, it is common to get reports of fruit quality problems, mainly due to maturity. Thus, the objective of this study was to develop calibration models for soluble solids content (SSC) and dry matter (DM) of ‘Palmer’ mangoes using portable (VIS-NIR) spectrometer. Interactance spectra were obtained with a portable F-750 spectrometer in the wavelength range of 306–1140 nm, 8 nm spectrum resolution, and 4 scans averaged per spectra. Spectra were used to develop SSC and DM models using partial least square regression (PLSR) with full cross validation. The best SSC calibration model was developed using spectra pre-processed with standard normal variate (SNV), first derivative of Savitzky–Golay and window of 699–999 nm. It was observed a RMSECV of 1.39%, with a RCV2 of 0.87, and RPD of 2.77. Better results were observed for the DM calibration model which was built with raw spectra using the window of 699–981 nm (RMSECV of 8.81 g kg−1, RCV2 of 0.84, and RPD of 2.51). Poor calibration models were obtained for firmness. The results indicated that portable VIS-NIR spectrometer can be used as a non-destructive technique to assess SSC and DM content for ‘Palmer’ mangoes. It is necessary to incorporate more sources of variation, to reduce RMSE values and improve robustness, especially for fruit SSC and DM prediction.
Keywords: Chemometrics; DM; Mangifera indica L.; PLSR; SSC; SWNIRS